Towards an Anti-Antiutopia: Solarpunk Cities and the Precarity of Our Urban Future - Crosby, Phillip (Enquiry The ARCC Journal for Architectural Research, 2023)
This paper examines Darko Suvin’s and Kim Stanley Robinson’s assertion that the late-stage capitalism and neoliberalism of our world can be understood as an “antiutopia” that actively works to suppress the imagination of better futures. It argues that the relatively new science fiction sub-genre of solarpunk—which sets itself in direct opposition to the dystopian visions of the more well-known subgenre cyberpunk and imagines worlds that focus on the community rather than the individual, on environmental sustainability rather than environmental degradation, on social justice rather than subjugation and inequality, and on optimism rather than nihilism—offers some of the most promising paths toward the rejection of this antiutopia in favor of an anti-antiutopian (and therefore utopian) approach that actively works to bring about a better future. The paper suggests that the solarpunk futures currently emerging in literature, art, and online communities offer architects, landscape architects, and urban designers powerful inspiration for the future of our increasingly urban world. It examines a selection of short stories, novels, films, and other media—as well as innovative projects of urbanism—for examples of how embracing the practical utopianism of solarpunk can provide both visions of better worlds and potential paths for achieving them.